(untitled) (International journal of artificial intelligence, 2024)
Advancements in technology have significantly transformed education, and biology, as a dynamic and experimental science, has greatly benefited from these innovations. This article explores how technology is reshaping biology education through tools like virtual laboratories, augmented reality (AR), gamification, and artificial intelligence (AI). We discuss the benefits, challenges, and implications of these methods for enhancing student engagement and comprehension. Future perspectives emphasize the integration of emerging technologies to create more inclusive and interactive learning environments.